The War on Terror (and Werewolves): Post-9/11 Horror and the Gothic Clash of Civilisations. Issue 2 (1st November 2015) - Unknown
Abstract : Twentieth century cinema involving monster conflict featured solitary monsters in combat ( Frankenstein Meets the Wolf Man, for example). The writing of Anne Rice and the RPG Vampire: The Masquerade by White Wolf Games introduced the idea of Gothic communities and civilisations in confl ict. It was not until after the terror attacks of 11 September that the idea of a 'clash of civilisations' between supernatural societies fully emerged into the mainstream of popular culture. This essay explores the construction of a 'clash of civilisations' between supernatural communities as a form of using the Gothic as a metaphor for contemporary terrorism infilm and television series such as Underworld, Twilight, True Blood and The Vampire Diaries . Inevitably, it is the lycanthropes that are the disempowered and disenfranchised society and are alternately exploited by and rebel against the dominant vampire civilisation grown decadent and on the verge of collapse. Post-9/11 Gothic posits a world in which vampire society is the new normal, and werewolves represent a hidden danger within. Lycanthropes must be controlled, profi led and/or fought and defeated. Through close readings of the cinematic and televisual texts, I explore the vampire/werewolf clash as metaphor and metonym for the war on terror.